PERANCANGAN SISTEM APLIKASI PEMINJAMAN DAN PENGEMBALIAN BUKU BERBASIS VB NET DAN ARDUINO DI PERPUSTAKAAN SMPN 1 JAYAKERTA - Siti Carminah; Ahmad Anas (Jurnal Komputer dan Teknologi, 2025)
The library is a learning facility that plays an important role in providing books as a reference source for students' learning both inside and outside KBM (Teaching and Learning Activities). The administration of borrowing and returning books in the SMPN 1 Jayakerta library is considered to be less effective and still uses recording in the library's master book so it is easily damaged or lost. Based on these problems, the author aims to design an application system for borrowing and returning library books at SMPN 1 Jayakerta using VB Net and Arduino. The results of research at SMPN 1 Jayakerta can be concluded that by building an application for borrowing and returning library books, it can help in the administration of borrowing and returning books more quickly and reduce data errors or double data and the risk of records being lost and make it easier for librarians to report to the school principal.